SEBARAN DAN KELIMPAHAN MAKROZOOBENTOS DI TELUK KUPANG, NUSA TENGGARA TIMUR - A. M. Pirzan; Utojo Utojo (Universitas Gadjah Mada, 2008)
The objectives of this research were to find out the distribution and abundance of macrozoobenthos in Kupang Bay and to evaluate the suitability of this water for mariculture activity in the future based on physical and chemical water properties. Samples were collected from 10 stations along shoreline of the bay. Water samples were collected by cammerer water sampler, while benthic organisms were collected by ekman dradge. Samples were transferred to laboratory to identify and analyze. The results showed that the diversity index of the macrozoobenthos was moderately stable, and there were 4 to 10 species found in each station of Kupang Bay. The species dominancy was ranged from 28-82%, and the most dominant was Nassarius pullus. The water quality indicated that the study site was suitable for mariculture activities. It leads to suggestion that for the seaweed and floating net cage culture should be located in the mouth of the bay, while for pearl culture should be located along channel between Semau and Timor Islands.